Dakwah strategy in Laos - Amafua, Mahfuth Khamis (2015)
Personal innovative strategy of how to do da'wah in Laos. Though the Muslim population is small but it is a promising one. The presentation also highlighted that there is a greater need for Da'wah works in Laos. Muslim NGOs should mobilize efforts to visit Laos for the Islamic propagation.